PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER) TERHADAP NET PROFIT MARGIN (NPM) - Devi Anggraini; Nurul Hasanah (Universitas La Tansa Mashiro, 2017)
This study aims to determine the effect of the Current Ratio (CR) of Debt to Equity Ratio (DER) on Net Profit Margin in Retail Trade Sub Sector Companies Listed on the Indonesia Stock Exchange for the 2011-2016 Period. The method used in this research is quantitative method, the sample is taken using the Purposive Sampling method, from the predetermined criteria the sample used as many as 7 companies and uses secondary data from the Indonesia Stock Exchange, namely the Retail Trade Sub Sector of the 2011-2016 period. Tests of statistics used are descriptive statistics testing, classical assumptions, multiple linear regression analysis, correlation analysis, coefficient of determination, hypothesis testing using the help of the SPSS V20 application program.Partial testing shows that the Current Ratio has a significant effect on Net Profit Margin with a tcount greater than ttable which is 3,675> 1,684 with a significant level of 0.001 <0.05, while the Debt to Equity Ratio has a significant effect on Net Profit Margin with a tcount greater than ttable namely -3,056> 1,684 with a significant level of 0.004 <0.05. Simultaneously Current Ratio and Debt to Equity Ratio have a significant effect on Net Profit Margin with the value of Fcount greater than Ftable which is 27.976> 2.84 with a significant level of 0.000 <0.05 and a coefficient of determination of 58.9%.